Knowledge, Attitude and Practice of Cervical Carcinoma Screening among Bangladeshi Women - Nur, Ayesha Najma; Bhowmik, Juthi; Chowdhury, Shiuly; Begum, Shirin Akter (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2021)
Background: The uterine cervix is the commonest site for female genital cancer. In developing countries, carcinoma cervix is the most common malignancy in females and a major public health problem. It is reported In Bangladesh that the prevalence of carcinoma cervix is 20% among all types of cancer affecting females. To determine the level of knowledge, attitude and practice among Bangladeshi women about screening of cervical carcinoma Materials and methods: A cross-sectional study was conducted on married women above the age of 20 years, attending OPD of Obstetrics & Gynecology, Medicine and Surgery of BSMMU from January 2013 to June 2013. By using purposive sampling technique 225 respondents were enrolled in the study. Results: Mean age of the respondents was 43.34 years with a standard deviation of ± 12.49 years. Most of the respondents (96%) were Muslim and from urban areas. More than two-thirds of the respondents (71.1%) were educated up to secondary level. More than 80% respondents were housewives. About three-fourth of the respondents were form middle class families. Only 20% could mention cervical cancer as the leading cancer among women. About 20% respondents knew that early and multiple marriages were the two risk factors for cervical cancer. Most of the respondents (93.3%) believed that cervical cancer is dangerous disease and was able to mention smoking as one of the important risk factors. About one-third respondents knew that terms Pap’s smear and VIA. But most of the respondents did not undergo any screening procedure under the assumption that the screening was not necessary. It was found that respondents with higher education level possessed good knowledge regarding cervical cancer. It was also true for respondents whose husbands were more educated. Higher education level was positively correlated with good attitude/practices. The respondents who had good knowledge about cervical cancer showed good attitude/practice regarding the same. Conclusion: The knowledge regarding cervical cancer among the participants was not satisfactory. Although most of the participants believed that cervical cancer is dangerous disease few really knew that it is preventable. Higher education level was positively correlated with good knowledge and good attitude/practices regarding cervical cancer. Long term education for women should be started to provide the needed information regarding cervical cancer screening. Chatt Maa Shi Hosp Med Coll J; Vol.20 (1); January 2021; Page 28-32